Editorial - International Journal of Sustainable Energy Planning and Management Vol 36 - Østergaard, Poul Alberg; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2022)
This 36th volume of the International Journal of Sustainable Energy Planning and Management starts at the global scale with a survey of the economy of the oil industry. Limitations of single-sector analyses of Chile is the focal point of a commentary on a previously published study in the journal Energies. The authors of the commentary find that limitations in literature survey, methodology, and data result in a significant underestimation of, e.g., the potential for photo voltaics. The potential for hydro power is affected by changes in water flows as analysed by Melo, which brings some level concern as hydro power is a key element in Brazil’s renewable energy exploitation effort. Lasty, Dall-Orsoletta et al. look into system dynamic models and whether they include social aspects in the modelling. This is only found in a minority of system dynamic models.